2018
DOI: 10.1090/conm/704/14165
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of ultrametric Banach algebras of strictly differentiable functions

Abstract: Let IK be an ultrametric complete field and let E be an open subset of IK of strictly positive codiameter. Let D(E) be the Banach IK-algebra of bounded strictly differentiable functions from E to IK, a notion whose definition is detailed. It is shown that all elements of D(E) have a derivative that is continuous in E. Given a positive number r > 0, all functions that are bounded and are analytic in all open disks of diameter r are strictly differentiable. Maximal ideals and continuous multiplicative semi-norms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…First, we generalize results obtained in [8] and [9] to some Banach algebras of uniformly continuous bounded functions which we call semi-compatible and C-compatible and which are related to the contiguity relation yet considered in these papers. Actually, considering such an algebra S, we describe interactions between the contiguity relation defined on ultrafilters on IE and maximal ideals or the multiplicative spectrum of S. We prove that the Shilov boundary of S is the multiplicative spectrum itself.…”
Section: Introduction and General Results In Topologymentioning
confidence: 80%
See 2 more Smart Citations
“…First, we generalize results obtained in [8] and [9] to some Banach algebras of uniformly continuous bounded functions which we call semi-compatible and C-compatible and which are related to the contiguity relation yet considered in these papers. Actually, considering such an algebra S, we describe interactions between the contiguity relation defined on ultrafilters on IE and maximal ideals or the multiplicative spectrum of S. We prove that the Shilov boundary of S is the multiplicative spectrum itself.…”
Section: Introduction and General Results In Topologymentioning
confidence: 80%
“…x − y has a limit when x and y tend to a separately. Following [9] the functions of E are called strictly differentiable.…”
Section: Algebras B L D Ementioning
confidence: 99%
See 1 more Smart Citation
“…In order to prove our main theorems we first need several basic results. In [5], [6], we have proved a proposition that we can easily generalize:…”
mentioning
confidence: 96%
“…In [2], [4], [5], [6] we studied several examples of Banach IK-algebras of functions and showed that for each example, each maximal ideal is defined by ultrafilters [1], [7], [8] and that each maximal ideal of finite codimension is of codimension 1: that holds for continuous functions [4] and for all examples of functions we examine in [2], [5], [6]. Thus, we can ask whether this comes from a more general property of Banach IK-algebras of functions, what we will prove here.…”
mentioning
confidence: 99%